Efficacy of Accelerated Streptokinase Infusion in the Treatment of St-Elevation Myocardial Infarction - Umer Shafiq; Muhammad Abdul Wahab; Syed Kashif- (Gandhara University, 2023)
OBJECTIVES To determine the efficacy of accelerated streptokinase (SK) in patients with acute ST-elevation myocardial infarction (STEMI). METHODOLOGY This Descriptive study was done in the Department of Cardiology, Hayatabad Medical Complex over a period of 6 months from august 2020 to February 2021. Age ranged between 35-70 years. Both males and females presenting with acute ST elevation MI, patients within 6 hours of the onset of chest pain were included in the study. RESULTS Among 144 patients age distribution was analyzed as 50(35%) patients were in age 35-50 years, and 94(65%) patients were in age 51-70 years. The mean age and standard deviation were 61± 8.19. Gender distribution was analyzed as 88(61%) patients were male and 56(39%) patients were female. Status of BMI was analyzed as 69(48%) patients had BMI ≤27 Kg/m2 and 75(52%) patients had BMI >27 Kg/m2. CONCLUSION The accelerated SK infusion regimen of 1.5 MU in 20 min is safe and well tolerated with significantly faster and higher clinical reperfusion rates, more preserved LV systolic function, less atrial and ventricular sustained arrhythmias, and less in-hospital and 1-year mortality rates in acute STEMI.